2021
DOI: 10.1002/er.6680
|View full text |Cite
|
Sign up to set email alerts
|

A concise review on alternative route of biodiesel production via interesterification of different feedstocks

Abstract: Environmental challenges and decreasing fossil reserves due to increased utilization of fossil fuels have propagated the importance of alternative energy sources. Increased biodiesel production promoted excess waste crude glycerol leading to environmental issues, thereby inhibiting the sustainability of the process. This review paper discusses the different types of feedstocks utilized to produce glycerol-free biodiesel by reacting with methyl acetate via interesterification. Methyl acetate is used as an advan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 126 publications
(237 reference statements)
0
10
0
Order By: Relevance
“…A global shortage of fossil fuel-derived energy, which accounts for 80% of the global energy supply, 1 has increased the relevance of renewable energy. Fatty acid alkyl esters (FAAEs, commonly used as biodiesel) can serve as a drop-in alternative to fossil fuel-based diesel fuel in compression−ignition engines.…”
Section: Introductionmentioning
confidence: 99%
“…A global shortage of fossil fuel-derived energy, which accounts for 80% of the global energy supply, 1 has increased the relevance of renewable energy. Fatty acid alkyl esters (FAAEs, commonly used as biodiesel) can serve as a drop-in alternative to fossil fuel-based diesel fuel in compression−ignition engines.…”
Section: Introductionmentioning
confidence: 99%
“…The current energy system for transportation is still based on fossil fuels whose utilization is not sustainable in the long term due to limited resources and negative impact on climate change related to the accumulation of CO2 in the atmosphere [1]. For these reasons, fossil fuels must be gradually substituted by other CO2 neutral renewable energetic sources.…”
Section: Introductionmentioning
confidence: 99%
“…Another drawback of the transesterification is that methanol, which is used as acyl acceptor, is insoluble in the reaction media; therefore the alcoholysis generally starts with high interfacial mass transfer resistances that require accurate mixing. Recently, it was also found that methanol could be incompatible with the long-term stability of several heterogeneous catalytic systems, therefore making the overall process less effective [1].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations